Strengthening and toughening of a multi-component lithium disilicate glass-ceramic by ion-exchange. Issue 13 (October 2020) - Li, X.C.; Meng, M.; Li, D.; Wei, R.; He, L.; Zhang, S.F.
Abstract: A multi-component lithium disilicate (LD) glass-ceramic with interlocking microstructure consisting of rod-like LD crystals and glassy matrix was ion-exchanged over wide temperature and time ranges in pure NaNO3 or mixed NaNO3 and KNO3 baths below the glass transition temperature. Treatment temperature, time and salt bath dependences of surface characteristics and mechanical properties for the ion-exchanged glass-ceramic were investigated. It was found that the glass-ceramic with limited glassy matrix could be remarkably strengthened and toughened in NaNO3 bath by adjusting the treatment temperature to a moderate level, at which Li + /Na + exchange between the glassy matrix and the salt bath could form an ion-exchanged layer with larger depth and less stress relaxation. Furthermore, by using the mixed salt bath, the undesirable exchange of K + /Na + in pure NaNO3 bath could be limited; further enhanced strengthening effect was achieved. The results might renew the interest on strengthening LD glass-ceramics by traditional ion-exchange process.